On the applications of a minimax theorem. (4th May 2022) - Ricceri, Biagio
Abstract : In this paper, we give an overview of some recent applications of a minimax theorem. These applications deal with: uniquely remotal sets in normed spaces; multiple global minima for the integral functional of the Calculus of Variations; multiple periodic solutions for Lagrangian systems of relativistic oscillators; variational inequalities in balls of Hilbert spaces.